Surgical Management of Tail Gangrene and Necrosis in Long-Tailed Male Kashmir Merino Sheep: A Retrospective Study - Shahid Hussain Dar; Mursaleen Rashid; Raja Aijaz Ahmad; Mudasir Bashir Gugjoo; Shabaz Shola; Syed Yufa; A Muhee (The Indian Veterinary Journal, 2026)
This retrospective study evaluated the etiology, clinicopathological patterns, and surgical management of tail gangrene and necrosis in 22 long-tailed male Kashmir Merino sheep presented to a teaching veterinary hospital between 2019 and 2024. The most common causes were dog bites (31.8%), flystrike (27.3%), crush injuries (18.2%), and malicious docking (13.6%), with the tail tip being the most frequently affected region (68.2%). Dry gangrene predominated (68%), whereas moist gangrene accounted for 32% of cases. A statistically significant association (p < 0.01) was observed between injury etiology and gangrene type, with traumatic ischemic injuries resulting in dry gangrene and contaminated wounds leading to moist gangrene. All animals underwent surgical tail amputation cranial to the affected tissue under posterior epidural anaesthesia, followed by standard antimicrobial and analgesic therapy. Complete recovery without postoperative complications was achieved in all cases (100%). The findings confirm tail amputation as an effective and welfare-oriented therapeutic intervention for advanced tail gangrene and emphasize the severe consequences of improper docking practices.